SENI PERTUNJUKAN WAYANG GOLEK SEBAGAI DAYA TARIK PARIWISATA BUDAYA DI SAUNG ANGKLUNG UDJO - Priyanto, Priyanto; Musthofa, Budiman Mahmud (Jurnal Vokasi Indonesia, 2020)
Wayang golek performance art combines elements of drama, sound, literature, music, movement and fine arts. It can be said that the art of wayang golek performance is a "noble" art and must be preserved. It is very interesting to observe the wayang golek performance art at Saung Angklung Udjo (SAU) which packs the show so that it can become one of the attractions of cultural tourism. This study aims to determine how the packaging of the wayang golek performance art in SAU so that it can attract and attract cultural tourism. Through qualitative research methods, it was found that the puppet show art at Saung Angklung was successfully packaged in a series of angklung performances so that it became an attractive tourist attraction. Although the duration of the puppet show is not as long as wayang performances in general, the cultural values and messages are easily accepted by the audience. The results of the research show that the management of the Saung Angklung Udjo show has succeeded in producing and creating various wayang and angklung performances continuously so that they can become an attraction for cultural tourism.